Co-chairs' Summary: Task Force on Telecommunications Infrastructure in the Arctic; meeting 3 - TFTIA (Arctic Council Secretariat, 2016)
Co-chairs' summary from the 3rd meeting of the Task Force on Telecommunications Infrastructure in the Arctic, held in Copenhagen, 7-8 September, 2016.